Pacific finance sector brief Marshall Islands. (Pacific finance sector briefs., 2019)
The Marshall Islands financial system is comprised of three main banks, two large money transfer operators, two insurance companies, and a pension fund. The stability of the countrys banking system faces risks on two fronts. One is the high level of household debt, which reached 60% of total employees compensation in 2018. The other is the possibility of the Marshall Islands losing its connections with US banks due to rising costs associated with complying to US anti terrorism financial rules. In response to these risks, the government is undertaking measures to strengthen financial regulations and prudential guidelines and is drafting new anti money laundering legislation.